Avenge but one of my two eyes (2005) - Mograbi, Avi ([United Kingdom] : Second Run DVD, 2006)
Shot in the Occupied Territories by Israeli director Avi Mograbi, this controversial documentary film draws parallels between the Israeli - Palestinian situation today and the enduring myths of Samson and Masada. Mograbi offers a powerful, at times chilling, lament of the continuing cycles of violence rooted in the past and threatening to engulf everyone's future. With the roots of so much real-world conflict left unexamined by today's restless media, this film reminds us just how vital filmmakers like Avi Mograbi are.
Hebrew, Arabic, English
Onderzoek KASK Professioneel (OFVP)
film
Keywords: Mograbi, Avi